Demographic Portrait of Corruptors in Indonesia - Khy’sh Nusri Leapatra Chamalinda; Tarjo Tarjo; Bambang Hariyadi (JAFFA, 2019)
Corruption not only cause financial losses to the state but also violates the social and economic rights of society at large. Corruption always draws more attention than other criminal acts (Hartanti, 2005). This research aims to present a demographic portrait of corruptors in Indonesia based on the Decree of Supreme Court of 2015. This research used qualitative method with descriptive analytical approach. There were 92 cases of corruption in the Decree of Supreme Court of 2015 and the number of corruptors analyzed was 106. Informants in this research were psychologists and religious experts. Data collection method for the primary data was interview and the secondary data collection method was investigating decree of Supreme Court documents. The results showed that the majority of corruptors in Indonesia were male (87%), Muslim (74%), aged between 46-55 years old (51%), undergraduates (34%), working as civil servants (45 %), serving as government officials or employees (56%), and working within the scope of government agencies (57%).